'Strategising' the India-EU Partnership. Issue 6 (2nd November 2022) - Buraga, Manoj Babu
Abstract: India's foreign policy, as in the case of any other sovereign state, aims at protecting and promoting the country's 'national interest.' Strategic autonomy, which has been its defining value and goal, remains at the core of India's global engagements. India maintains political, diplomatic, economic, strategic, science and technological, and cultural relations to achieve a stable, secure, peaceful, and prosperous India. The largest 'democracy' in the world, India, joins hands with the EU, the largest cluster of 'democracies' in the world. This article provides a chronology of India–EU interactions from the inception and intent to explore their strategic partnership. It examines India–EU strategic partnership significance, and differences, and highlights whether the strategic partnership 'strategized' enough or not. India and the EU are two quite exceptional entities in the world; thus, their strategic partnership is really a 'true strategic alliance'.